Regulation of GSK-3 activity by curcumin, berberine and resveratrol: Potential effects on multiple diseases. (August 2017) - McCubrey, James A.; Lertpiriyapong, Kvin; Steelman, Linda S.; Abrams, Steve L.; Cocco, Lucio; Ratti, Stefano; Martelli, Alberto M.; Candido, Saverio; Libra, Massimo; Montalto, Giuseppe; Cervello, Melchiorre; Gizak, Agnieszka; et al.
Abstract: Natural products or nutraceuticals promote anti-aging, anti-cancer and other health-enhancing effects. A key target of the effects of natural products may be the regulation of the PI3K/PTEN/Akt/mTORC1/GSK-3 pathway. This review will focus on the effects of curcumin (CUR), berberine (BBR) and resveratrol (RES), on the PI3K/PTEN/Akt/mTORC1/GSK-3 pathway, with a special focus on GSK-3. These natural products may regulate the pathway by multiple mechanisms including: reactive oxygen species (ROS), cytokine receptors, mirco-RNAs (miRs) and many others. CUR is present the root of turmeric ( Curcuma longa ). CUR is used in the treatment of many disorders, especially in those involving inflammatory processes which may contribute to abnormal proliferation and promote cancer growth. BBR is also isolated from various plants ( Berberis coptis and others) and is used in traditional medicine to treat multiple diseases/conditions including: diabetes, hyperlipidemia, cancer and bacterial infections. RES is present in red grapes, other fruits and berries such as blueberries and raspberries. RES may have some anti-diabetic and anti-cancer effects. Understanding the effects of these natural products on the PI3K/PTEN/Akt/mTORC1/GSK-3 pathway may enhance their usage as anti-proliferative agent which may be beneficial for many health problems.